Wound Treatment Using Aloevera in the Process of Accelerating Wound Healing for Post-Op Patients at the Lompe Ntodea Community Health Center - Moh Rozani; Denny Susanto; Mohammad Fauzi; Adrian Sali (STRADA : Jurnal Ilmiah Kesehatan, 2024)
The high incidence of wounds in Indonesia means that effective and efficient wound care is needed, therefore one good wound treatment is to use Aloevera as a medicine and provide protein nutrition as a nutritional intake for wounds. The aim of this research is to find out how fast the process of wound tissue growth is using Aloevera gel. This research method uses a case study approach on post-operative patients. Wound care procedures were carried out 22 times using aloe vera gel. Wound care techniques used are tissue management inflammation and infection control, moisture balance, epithelial (TIME). The measuring tool in this research used the Bates Jensen Wound Assessment Tool (BWAT) observation tools.